Extensive subdural hematoma in full term neonate due to falcine laceration - V. Umamaheswara Reddy; Amit Agrawal; H. Suryaprakash; Vankineni Srikanth; G. Mithilasri (SpringerOpen, 2015)
Subdural hematoma in supratentorial location occur due to rupture of bridging veins or by laceration of falx, the latter entity being extremely uncommon cause of hemorrhage in full term new-born neonate who has been delivered by non-instrumental vaginal delivery. Compressive effects on the fetal parietal bones by rigid maternal pelvic structures result in frontal-occipital elongation and vertical or oblique molding. This in turn causes cranio-caudal stretching of both the falx and tentorium. Normally the give-away is at the falcine and tentorial junctions, rarely only falcine laceration can result. Most of massive subdural hematomas due to falx laceration, tentorial laceration or occipital diastasis have a rapid lethal course or patients may have permanent neurological disability. We describe a case of full term neonate who had extensive subdural and parenchymal hemorrhage resulting from falcine tear.